Tracing the Genesis of Contagion in the Oil-Finance Nexus - Scott M. R. Mahadeo; Reinhold Heinlein; Gabriella Deborah Legrenzi (Center for Economic Studies and ifo Institute (CESifo), 2019)
A new procedure to trace the sources of contagion in the oil-finance nexus is proposed. We do this by consolidating veteran rules derived from the empirical oil literature to filter oil supply, global demand, and oil demand shocks into discrete typical and extreme conditions. We show how these identified conditions can then be used to determine the stable and extreme sub-samples for comparing market relationships in the construction of contagion tests. Our original approach is useful for systemic risk assessment in countries vulnerable to oil market shocks. We illustrate the procedure using the dynamic relationships between the international crude oil market and the financial markets of a small oil-exporter.
Keywords: C32; E37; Q43; 330; contagion; correlation; exchange rate; oil; stock market